A 300-kb microduplication of 7q36.3 in a patient with triphalangeal thumb-polysyndactyly syndrome combined with congenital heart disease and optic disc coloboma: a case report - Anna Zlotina; Olesia Melnik; Yulia Fomicheva; Rostislav Skitchenko; Alexey Sergushichev; Elena Shagimardanova; Oleg Gusev; Guzel Gazizova; Tatiana Loevets; Tatiana Vershinina; Ivan Kozyrev; Mikhail Gordeev; et al. (BMC, 2020)
Abstract Background Triphalangeal thumb-polysyndactyly syndrome (TPT-PS) is a rare well-defined autosomal dominant disorder characterized by long thumbs with three phalanges combined with pre- and postaxial polydactyly/syndactyly of limbs. By now, the syndrome has been reported in several large families from different ethnic backgrounds, with a high degree of inter- and intrafamilial variability. The genome locus responsible for TPT-PS has been mapped to the 7q36.3 region harboring a long-range sonic hedgehog (SHH) regulatory sequence (ZRS). Both single-nucleotide variants and complete duplications of ZRS were shown to cause TPT-PS and similar limb phenotypes. TPT-PS usually forms as isolated limb pathology not associated with additional malformations, in particular, with cardiovascular abnormalities. Case presentation Here we report on a rare Russian neonatal case of TPT-PS combined with severe congenital heart disease, namely double outlet right ventricle, and microphthalmia with optic disc coloboma. Pedigree analysis revealed TPT-PS of various expressivity in 10 family members throughout five generations, while the cardiac defect and the eye pathology were detected only in the proband. To extend the knowledge on genotype-phenotype spectrum of TPT-PS, the careful clinical and genomic analysis of the family was performed. High-resolution array-based comparative genomic hybridization (array-CGH) revealed a ~ 300 kb microduplication of 7q36.3 locus (arr[GRCh37] 7q36.3(156385810_156684811) × 3) that co-segregated with TPT-PS in the proband and her mother. The duplication encompassed three genes including LMBR1, the intron 5 of which is known to harbor ZRS. Based on whole-exome sequencing data, no additional pathogenic mutations or variants of uncertain clinical significance were found in morbid cardiac genes or genes associated with a microphthalmia/anophthalmia/coloboma spectrum of ocular malformations. Conclusions The results support the previous data, indicating that complete ZRS duplication underlies TPT-PS, and suggest a broader phenotypic impact of the 7q36.3 microduplication. Potential involvement of the 7q36.3 microduplication in the patient's cardiac and eye malformations is discussed. However, the contribution of some additional genetic/epigenetic factors to the complex patient`s phenotype cannot be excluded entirely. Further comprehensive functional studies are needed to prove the possible involvement of the 7q36.3 locus in congenital heart disease and eye pathology.